2014
DOI: 10.1039/c4ee00749b
|View full text |Cite
|
Sign up to set email alerts
|

Results of a 20 000 h lifetime test of a 7 kW direct methanol fuel cell (DMFC) hybrid system – degradation of the DMFC stack and the energy storage

Abstract: First-ever lifetime test of a DMFC system lasting 25 600 h with a dynamic load profile of a material handling vehicle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…The degradation rate was only 5 mV h À1 at 120 mA cm À2 which accounted for a total power density loss of 14%. Recently, Kimiaie et al [35] reported ground breaking results where they demonstrated a successful lifetime operation of DMFC stack for 20,000 h integrated in a hybrid energy system for powering a forklift truck. The results of their study present a vital achievement regarding the durability of DMFC systems that has been a matter of serious concern.…”
Section: Current Status Of Operational Durability Of Dmfcsmentioning
confidence: 97%
“…The degradation rate was only 5 mV h À1 at 120 mA cm À2 which accounted for a total power density loss of 14%. Recently, Kimiaie et al [35] reported ground breaking results where they demonstrated a successful lifetime operation of DMFC stack for 20,000 h integrated in a hybrid energy system for powering a forklift truck. The results of their study present a vital achievement regarding the durability of DMFC systems that has been a matter of serious concern.…”
Section: Current Status Of Operational Durability Of Dmfcsmentioning
confidence: 97%
“…Carbon-based fuels can be used in fuel cells (FCs) [1][2][3][4][5][6] for the production of electricity -despite their relatively low gravimetric energy density compared to molecular hydrogen, 33 kWh kg −1 vs. 1-9 kWh kg −1 -or in electrolysis cells (ECs) [7][8][9][10][11] for the production of fuels and/or chemicals. For FCs, the main selection criterion for the design and fabrication of electrode materials is the electrooxidation with the lowest overpotential, i.e., at low electrode potentials (E), ideally E < 0.7 V vs. reversible hydrogen electrode (RHE).…”
mentioning
confidence: 99%
“…Among all the available energy conversion options, fuel cells appear to be more promising because of their ability to convert chemical energy into electrical energy in an efficient and non-polluting way [6]. Due to their high energy and power density, both proton-exchange membrane fuel cells (PEMFC) and direct methanol fuel cells (DMFC) have shown promising results for their application as energy conversion sources for high-end electronic devices and electric vehicles [7,8]. Electrochemical oxygen reduction reaction (ORR) has already been realized as a key aspect in areas like energy storage and energy conversion, and therefore, oxygen reduction reaction surely plays a pivotal role in facilitating an energy conversion process inside a typical fuel cell [9].…”
Section: Introductionmentioning
confidence: 99%